Additives Altered Bacterial Communities and Metabolic Profiles in Silage Hybrid Pennisetum - Tian, Hanchen; Zhu, Yanchen; Dai, Mengxue; Li, Tong; Guo, Yongqing; Deng, Ming; Sun, Baoli (Frontiers in Microbiology, 2022)
This study was conducted to investigate the effects of different additives on the fermentation quality, nutrient composition, bacterial communities, and metabolic profiles of the silage of hybrid Pennisetum. The experiment was conducted using five treatments, i.e., CK, control group, MA, 1% malic acid of fresh matter (FM) basis, GL, 1% glucose of FM basis, CE, 100 U/g FM cellulase, and BS, 106 cfu/g FM Bacillus subtilis, with six replicates each treatment. After a 120-day fermentation, 30 silage packages were opened for subsequent determination. As a result, all four additives had positive effects on the fermentation quality and nutrient composition of the silage of hybrid Pennisetum. The high-throughput sequencing of V3–V4 regions in 16S rRNA was performed, and results showed that Firmicutes and Proteobacteria were the dominant phyla and that Aquabacterium and Bacillus were the dominant genera. MA, GL, CE, and BS treatment resulted in 129, 21, 25, and 40 differential bacteria, respectively. The four additives upregulated Bacillus smithii but downregulated Lactobacillus rossiae. Metabolic profiles were determined by UHPLC-Q/TOF-MS technology and the differential metabolites caused by the four additives were 47, 13, 47, and 18, respectively. These metabolites played antioxidant, antibacterial, and anti-inflammatory functions and involved in pathways, such as the citrate cycle, carbon fixation in photosynthetic organisms, and glyoxylate and dicarboxylate metabolism. In conclusion, silage additives promoted fermentation quality and nutrient composition by altering bacterial communities and metabolic profiles. This study provided potential biomarkers for the improvement of silage quality.